The Pecheneg Settlement along Hungary’s Northwestern Frontier - Sarolta Tatar (Acta Mongolica, 2014)
The intention of this paper is to describe one way of medieval contacts between Hungary and the Orient, namely how the Turkic speaking Pecheneg guards were settled in three counties, Moson, Sopron and Győr along the Western frontier of the Hungarian Kingdom. A method that compares written sources to historical geography will be used here. This method is applicable when researching the Hungarian Middle Ages, since early medieval Hungarian settlements were often named after the owner, or the tribe that settled there. Therefore, besides written documents, maps of medieval Hungary might reveal additional information about social and military organizations.